PREFERENSI RESIKO DALAM MEMODERASI PEMAHAMAN PERATURAN PERPAJAKAN DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN FORMAL PADA KPP MAKASSAR UTARA - Asbi Amin (AkMen JURNAL ILMIAH, 2018)
This research aimed to test the understanding of the tax rules, tax paying awareness to tax formal compliance. This research also to test the effect of risk preferences which acts as a moderating variable on the relationship between the understandings of the tax rules and tax paying awareness on tax formal compliance. Data used in this research were obtained from questionnaires (primary) and a few observations and interview with parties related. Methods of data analysis using moderate regression analysis.Results of research indicates that an understanding of the tax laws and tax paying awarenesseffect the positive and significant to tax formal compliance. The risk preferences showed the positive and significant result so that can moderate the relationship between the understanding of the tax laws and taxpayer formal compliance.The risk preferences showed the positive and significant result so that can moderate the relationship between the understanding of tax paying awareness and taxpayer formal compliance.